Supplier Selection on Performance of Manufacturing Industries in Uganda: A Case Study of Hot Loaf in Kabale Municipality. - Atwongyeire, Naume (Kabale University, 2024)
The performance of the manufacturing sector as a whole in Uganda has been affected by the use of obsolete supply chain management practices and technologies with a poor state of physical infrastructure, limited research and development, poor institutional framework, and inadequate supply chain evaluation, technical, and procurement skills. Statistics. The general objective of the study was to investigate the effects of supplier selection on the performance of the manufacturing industry in Uganda; a case of Hot loaf in Kaba le Municipality.